Pollyanna - Porter, Eleanor H. (Eleanor Hodgman), 1868-1920. (New York : Dell, 1990)
Unwanted and unloved, Pollyanna Whittier comes to her aunt's home without a warm welcome. Pollyanna's irrepressible spirits make punishments seem like treats and her cheerfulness brings happiness to her aunt and other members of the community.
Despite many hardships and the loss of her father, Pollyanna always seems to make the best of each situation.
5.6
5-8
Keywords: Aunts -- Fiction; Orphans -- Fiction; Aunts -- Fiction; Orphans -- Fiction